One Health in Nepal- An Overview - Khatiwada, Abishkar; Karna, Alina; Bhat, Neeti; Deo, Satish (Nepal Journal of Health Sciences, 2021)
In order to meet today’s complex health and environmental challenges, multi-disciplinary research has never been more exigent. Nepal is in the early stages of adopting One Health (OH), but it is continuously expanding. Various initiatives have been taken by the Government of Nepal (GoN) to combat problems such as antimicrobial resistance, highly pathogenic avian influenza and rabies using an integrated health approach, but several challenges remain in their implementation. A few of the major obstacles to implementing OH in Nepal include weak organizational structure to support the initiative, no legal framework required to implement OH, insufficient technical expertise, lack of intersectoral data sharing mechanisms, a limited budget, and poor legislative understanding. To address these gaps and prioritize the health problems where OH will lead to the best outcome, we encourage GoN to address the gaps. To control the ongoing COVID-19 pandemic, the rational application of the One Health strategy should be our utmost priority. The One Health paradigm can help healthcare professionals and researchers improve the public’s health in response to the coming wave of COVID-19 pandemic and prepare for future pandemics.